Can a Shockable Initial Rhythm Identify Out-of-Hospital Cardiac Arrest Patients with a Short No-flow Time?. (January 2021) - Cournoyer, Alexis; de Montigny, Luc; Potter, Brian J.; Segal, Eli; Chauny, Jean-Marc; Lamarche, Yoan; Cossette, Sylvie; Morris, Judy; Albert, Martin; Denault, André; Paquet, Jean; Marquis, Martin; et al.
Abstract: Aims: Initial shockable rhythms may be a marker of shorter duration between collapse and initiation of cardiopulmonary resuscitation, known as no-flow time (NFT), for patients suffering an out-of-hospital cardiac arrest (OHCA). Eligibility for extracorporeal resuscitation is conditional on a short NFT. Patients with an unwitnessed OHCA could be candidate for extracorporeal resuscitation despite uncertain NFT if an initial shockable rhythm is a reliable stand-in. Herein, we sought to describe the sensitivity and specificity of an initial shockable rhythm for predicting a NFT of five minutes or less. Methods: Using a registry of OHCA in Montreal, Canada, adult patients who experienced a witnessed non-traumatic OHCA, but who did not receive bystander cardiopulmonary resuscitation, were included. The sensitivity and specificity of an initial shockable rhythm for predicting a NFT of five minute or less were calculated. The association between the NFT and the presence of a shockable rhythm was evaluated using a multivariable logistic regression. Results: A total of 2450 patients were included, of whom 863 (35%) had an initial shockable rhythm and 1085 (44%) a NFT of five minutes or less. The sensitivity of an initial shockable rhythm to predict a NFT of five minutes or less was 36% (95% confidence interval [95%CI] 33–39), specificity was 66% (95%CI 63–68), the positive likelihood ratio was 1.05 (95%CI 0.94–1.17) and the negative likelihood ratio of 0.97 (95%CI 0.92–1.03). The probabilities of observing a shockable rhythm stayed stable up to 15 minutes, while the probabilities of observing a PEA lowered rapidly initially. Longer NFT were associated with lower odds of observing an initial shockable rhythm (adjusted odds ratio = 0.97 [95%CI 0.94–0.99], p = 0.012). Conclusions: An initial shockable rhythm is a poor predictor of a short NFT, despite there being an association between the NFT and the presence of a shockable rhythm.